2. Q2d
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log\sqrt[3]{45} </code></p>
Similar Question 2
<p>Express each of the following as a logarithm of a product of quotient.</p><p><code class='latex inline'> \displaystyle \log_67 + \log_68 + \log_69 </code></p>
Similar Question 3
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log\sqrt[3]{45} </code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Use the laws of logarithms to express each of the following int terms of <code class='latex inline'>\log_b x , \log_by</code>, and <code class='latex inline'>\log_bz</code>.</p><p><code class='latex inline'> \displaystyle \log_bxyz </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \ln(\frac{x^3\sqrt{x - 1}}{3x + 4}) </code></p>
<p>Express each of the following as a logarithm of a product of quotient.</p><p><code class='latex inline'> \displaystyle \log_67 + \log_68 + \log_69 </code></p>
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log_7(36)^{0.5} </code></p>
<p>Use the laws of logarithms to express each side of the equation as a single logarithm. Then compare both sides of the equation to solve.</p><p><code class='latex inline'> \displaystyle \log_5x - \log_58 = \log_56 + 3\log_52 </code></p>
<p>Use the laws of logarithms to simplify and then evaluate each expression.</p><p><code class='latex inline'> \displaystyle \log_44^7 </code></p>
<p>Simplify</p><p><code class='latex inline'> \displaystyle (\log_881+\log_{\frac{1}{8}}3)(\log_881-\log_{\sqrt{8}}3) </code></p>
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log_37^{-1} </code></p>
<p>Express each of the following as a logarithm of a product of quotient.</p><p><code class='latex inline'> \displaystyle \log_410 + \log_412 - \log_420 </code></p>
<p>Use the laws of logarithms to simplify and then evaluate each expression.</p><p><code class='latex inline'> \displaystyle \log \sqrt{10} </code></p>
<p>Express each of the following as a logarithm of a product of quotient.</p><p><code class='latex inline'> \displaystyle \log_66\sqrt{6} </code></p>
<p>Use the laws of logarithms to express each side of the equation as a single logarithm. Then compare both sides of the equation to solve.</p><p><code class='latex inline'> \displaystyle \log_7x = 2 \log_7 25 - 3\log_7 5 </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \log_{2}(\frac{x(x + 1)}{\sqrt{x^2 - 1}}) </code></p>
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log\sqrt[3]{45} </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \log\sqrt{\frac{x^2 + 4}{(x^2 + 1)(x^3 - 7)^2}} </code></p>
<p>Simplify</p><p><code class='latex inline'> \displaystyle (\log_{49}\sqrt{125})(\log_5\sqrt[3]{7}) </code></p>
<p>Write the expression as a sum of difference of logarithms.</p><p><code class='latex inline'> \displaystyle \log_m(\frac{p}{q}) </code></p>
<p>Use the laws of logarithms to express each side of the equation as a single logarithm. Then compare both sides of the equation to solve.</p><p><code class='latex inline'> \displaystyle \log_2 x = 2\log_2 7 +\log_2 5 </code></p>
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log 5^2 </code></p>
<p>Write <code class='latex inline'>g(x)</code> in terms of <code class='latex inline'>f(x)</code> when <code class='latex inline'>f(x) = \log_2x</code> to the graph <code class='latex inline'>g(x) = \log_2(8x^3)</code>.</p>
<p>Use the laws of logarithms to simplify and then evaluate each expression.</p><p><code class='latex inline'> \displaystyle \log_3135 - \log_35 </code></p>
<p>Express each of the following as a logarithm of a product of quotient.</p><p><code class='latex inline'> \displaystyle \log_67 + \log_68 + \log_69 </code></p>
<p>Write the expression as a sum of difference of logarithms.</p><p><code class='latex inline'> \displaystyle \log_{2}(14 \times 9) </code></p>
<p>Write each expression as a single log.</p><p><code class='latex inline'> \displaystyle \log_43 + \frac{1}{2}\log_48 -\log_42 </code></p>
<p>Write each expression as a single log.</p><p><code class='latex inline'> \displaystyle 3\log_{5}2 + \log_{5}7 </code></p>
<p>Use the laws of logarithms to express each side of the equation as a single logarithm. Then compare both sides of the equation to solve.</p><p><code class='latex inline'> \displaystyle \log_3x = 2 \log_3 10 - \log_325 </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \log\sqrt[4]{x^2 + y^2} </code></p>
<p>Write the expression as a sum of difference of logarithms.</p><p><code class='latex inline'> \displaystyle \log (\frac{123}{31}) </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \log(\frac{x^3y^4}{z^6}) </code></p>
<p>Write the expression as a difference of logarithms.</p><p><code class='latex inline'> \displaystyle \log_4 (\frac{81}{30}) </code></p>
<p>Write the expression as a sum of difference of logarithms.</p><p><code class='latex inline'> \displaystyle \log(45 \times 68) </code></p>
<p>Use the laws of logarithms to simplify and then evaluate each expression.</p><p><code class='latex inline'> \displaystyle \log_510 + \log_52.5 </code></p>
<p>Express each of the following in the form <code class='latex inline'>r \log_ax</code>.</p><p><code class='latex inline'> \displaystyle \log_mp^q </code></p>
<p> Use the Laws of Logarithms to expand the expression fully.</p><p><code class='latex inline'> \displaystyle \ln(x\sqrt{\frac{y}{z}}) </code></p>
How did you do?
I failed
I think I failed
I think I got it
I got it
Another question?
Found an error or missing video? We'll update it within the hour! 👉
Report it
Save videos to My Cheatsheet for later, for easy studying.